2004
DOI: 10.1002/pola.20168
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermomechanical properties of epoxy resins modified by octafunctional cubic silsesquioxane epoxides

Abstract: The thermomechanical properties of octafunctional cubic silsesquioxane‐modified epoxy resins associated with dicycloaliphatic hardener (4,4′‐dimethyldiaminodicyclo hexyl methane) were studied using thermogravimetric analysis, differential scanning calorimetry, and dynamic mechanical analysis. The structures of epoxy resin containing cubic silsesquioxane epoxides were characterized by Fourier transform infrared spectroscopy and wide‐angle X‐ray scattering techniques. In this work, octa(dimethylsiloxybutylepoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
63
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 30 publications
5
63
0
Order By: Relevance
“…It has been found that the glass transition temperature of POSSreinforced epoxy nanocomposites either increases, 24,28,29,35,38 decreases, 27,31,[38][39][40] stays unchanged, 30,32,37,39 , or even disappears 37 with the addition of POSS depending on the chemical structure of the functional group (R group) on the POSS and the POSS loading. In general, the glass transition temperature of the nanocomposites decreases when the R group on the POSS is long and flexible and a ''soft'' interface can be formed between the nanoparticle and matrix; 27,32,40,45 on the other hand, T g increases if the interface is rigid and the polymer chain motions are hindered by their covalent bonding to POSS clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the glass transition temperature of POSSreinforced epoxy nanocomposites either increases, 24,28,29,35,38 decreases, 27,31,[38][39][40] stays unchanged, 30,32,37,39 , or even disappears 37 with the addition of POSS depending on the chemical structure of the functional group (R group) on the POSS and the POSS loading. In general, the glass transition temperature of the nanocomposites decreases when the R group on the POSS is long and flexible and a ''soft'' interface can be formed between the nanoparticle and matrix; 27,32,40,45 on the other hand, T g increases if the interface is rigid and the polymer chain motions are hindered by their covalent bonding to POSS clusters.…”
Section: Introductionmentioning
confidence: 99%
“…20 mol %), the glass transition of epoxy/octa(dimethylsiloxy butyl) epoxide nanocomposites disappears as measured by dynamic mechanical analysis (DMA) or differential scanning calorimetry (DSC) due to restricted segmental motion caused by the rigid POSS cage and a very high crosslink density. 37 The moduli of the POSS-filled nanocomposites similarly depend on the POSS structures. The glassy modulus of the nanocomposites is found to either increase due to the nanoreinforcement of the nanoparticles 27,31,39 or decrease; 37 furthermore, the rubbery modulus also either increases presumably due to the increased crosslink density or the reinforcement of the nanoparticles 28,30,43 or decreases due to the decreased crosslink density associated with the flexible structure of the POSS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, EP thermosets, like most polymers, lack thermal resistance and flame retardancy, particularly in certain applications where flame retardancy is a most required feature. The modification of EP via POSS could endow the materials improved thermal and oxidative resistance, flame retardancy, and dielectric properties [9][10][11][12][13][14][15]. Several studies on POSS modified epoxy resins were reported in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…They are the most commonly used engineering thermosets because of their good to excellent engineering properties [3][4][5], and as organic matrix it has excellent heat, moisture, and chemical resistant and good adhesion to many substrates [6,7].…”
Section: Introductionmentioning
confidence: 99%